If it's not what You are looking for type in the equation solver your own equation and let us solve it.
X in (-oo:+oo)
(-1/4)*X+72 = 9-2*X // - 9-2*X
(-1/4)*X-(-2*X)-9+72 = 0
(-1/4)*X+2*X-9+72 = 0
7/4*X+63 = 0 // - 63
7/4*X = -63 // : 7/4
X = -63/7/4
X = -36
X = -36
| 6(1-2/3x) | | -4x-25=8 | | 14x=3.50 | | -46+x=-4x+79 | | .75-9p=.6 | | 4x-194=70-8x | | .74-9p=.6 | | -76-4x=92-10x | | 4y=-3(2-2y)-4 | | -75+9x=x+85 | | -97+10x=137-3x | | t(9-2)=117 | | t(9+2)=117 | | -37-6x=26-9x | | 3x+x=4000000 | | 2x-11=28-x | | 5(2x+7)=11+4x | | 12.50x+0= | | -6x-7=9+(-2x) | | 1/25h^2=16 | | -6x-7=9+(-2) | | 2-2=13x+10x | | 12.50X+100Y= | | 6x+x=28000000 | | 9+5(3-3h)-2h= | | (x-1/4)=(7/8) | | 4z=1.4+4.2 | | x^5=17.8 | | 5x=2(3x-7)+12 | | 4(q+8)-36= | | f(x)=5x^2-40x+75 | | x+x+3x+45=180 |